Surface roughness as a comparator for natural teak alternatives - Chen, Alethea Mei Yun (Nanyang Technological University, 2021)
This study is about wood used for furniture. Natural teak has been a top choice for furniture makers due to its high strength and durability. However, its declining sustainability has generated the need for potential alternatives such as plantation teak, iroko and balau. While these woods may have comparable strength with natural teak, not much has been analysed about their surface roughness. This is important in determining their surface finish and durability as a piece of furniture. Hence, the objective of this study is to measure and compare the surface roughness of natural teak, plantation teak, iroko and balau based on these four parameters – arithmetic mean roughness, root-mean-square roughness, skewness and kurtosis. Based on the results, natural teak does possess a generally smooth surface with high durability. Its best alternative, based on the closeness and desirability of results, is balau. The surface profile of plantation teak has shown to be the most valley-based, which is ideal for coating and lubricating furniture. Iroko, on the other hand, has the roundest profile that makes it extremely durable due to lower levels of stress.